(untitled) - Mody, N. H. N. (Rutland, Vt., 1967)
This unique volume is indeed a must for the complete collector of Japanese art. Originally published in 1932, it was limited to a mere 200 copies in its first and only printing.
Keywords: Clock and watch making,Đồng hồ và đồng hồ báo thức; Japan,Nhật Bản